2015
DOI: 10.1103/physrevd.91.044003
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional Lifshitz-type spacetimes, universal horizons, and black holes in Hořava-Lifshitz gravity

Abstract: In this paper, we present all [(d + 1) + 1]-dimensional static diagonal vacuum solutions of the non-projectable Hořava-Lifshitz gravity in the IR limit, and show that they give rise to very rich Lifshitz-type structures, depending on the choice of the free parameters of the solutions. These include the Lifshitz spacetimes with or without hyperscaling violation, Lifshitz solitons, and black holes. Remarkably, even the theory breaks explicitly the Lorentz symmetry and allows generically instantaneous propagation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 109 publications
1
11
0
Order By: Relevance
“…Since they were first discovered in [202,215], universal horizons have been studied intensively, and already attracted lots of attention. These include universal horizons in static spacetimes [123,[218][219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234], and the ones with rotation [217,235,236] 25 . In particular, it was showed that universal horizons exist in the 24 To avoid theČerenkov effects, in the khronometric theory, or more general, in the Einstein-aether theory, c φ is required to be no less than the speed of light c φ ≥ c [203].…”
Section: )mentioning
confidence: 99%
“…Since they were first discovered in [202,215], universal horizons have been studied intensively, and already attracted lots of attention. These include universal horizons in static spacetimes [123,[218][219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234], and the ones with rotation [217,235,236] 25 . In particular, it was showed that universal horizons exist in the 24 To avoid theČerenkov effects, in the khronometric theory, or more general, in the Einstein-aether theory, c φ is required to be no less than the speed of light c φ ≥ c [203].…”
Section: )mentioning
confidence: 99%
“…For additional studies of these solutions, see [24][25][26][27]. In this case one adds a negative cosmological constant Λ to the action above…”
Section: Asymptotically Lifshitz Solutionsmentioning
confidence: 99%
“…Actually, it was found that HL gravity is a minimal holographic dual for the field with Lifshitz scaling [25]. Our recent works [26,27] found that various Lifshitz spacetimes are possible even without matter fields. Therefore, in principle, extension of the cMERA to modified gravity is possible.…”
Section: Conclusion and Discussionmentioning
confidence: 98%